Biomechanical studies of different numbers and positions of cage implantation on minimally invasive transforaminal interbody fusion: A finite element analysis - Han, Zhenchuan; Ma, Chao; Li, Bo; Ren, Bowen; Liu, Jianheng; Huang, Yifei; Qiao, Lin; Mao, Keya (Frontiers in Surgery, 2022)
Background The position and number of cages in minimally invasive transforaminal interbody fusion (MIS-TLIF) are mainly determined by surgeons based on their individual experience. Therefore, it is important to investigate the optimal number and position of cages in MIS-TLIF. Methods The lumbar model was created based on a 24-year-old volunteer's computed tomography data and then tested using three different cage implantation methods: single transverse cage implantation (model A), single oblique 45° cage implantation (model B), and double vertical cage implantation (model C). A preload of 500 N and a moment of 10 Nm were applied to the models to simulate lumbar motion, and the models' range of motion (ROM), ROM ratio, peak stress of the internal fixation system, and cage were assessed. Results The ROM ratios of models A, B, and C were significantly reduced by >71% compared with the intact model under all motions. Although there were subtle differences in the ROM ratio for models A, B, and C, the trends were similar. The peak stress of the internal fixation system appeared in model B of 136.05 MPa (right lateral bending), which was 2.07 times that of model A and 1.62 times that of model C under the same condition. Model C had the lowest cage stress, which was superior to that of the single-cage model. Conclusion In MIS-TLIF, single long-cage transversal implantation is a promising standard implantation method, and double short-cage implantation is recommended for patients with severe osteoporosis.